Analyzing Food Science Research for Publishing Characteristics as a Model for Understanding the Needs of Researchers. Issue 4 (1st October 2020) - Salisbury, Lutishoor; Smith, Jeremy J.; Omotola Omolewu, Abayomi
Abstract: This paper provides a methodology to study the characteristics of the research output from a university department. The faculty publications and their cited references over a 10-year period were used as the basis for this study to identify their publishing patterns and the types of material they are publishing; a core set of journals and other resources they are publishing in and citing over this period; the characteristics of the journals in which they publish and cite; the degree of openness of their publications and their citation advantage; and the age of resources that are referenced.